1992
DOI: 10.1111/j.1432-1033.1992.tb16965.x
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence studies of the binding of bacteriophage M13 gene V mutant proteins to polynucleotides

Abstract: This investigation describes how the binding characteristics of the single-stranded DNA-binding protein encoded by gene V of bacteriophage M13, are affected by single-site amino acid substitutions.The series of mutant proteins tested includes mutations in the purported monomer-monomer interaction region as well as mutations in the DNA-binding domain at positions which are thought to be functionally involved in monomer-monomer interaction or single-stranded DNA binding. The characteristics of the binding of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
27
1

Year Published

1994
1994
1997
1997

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 41 publications
8
27
1
Order By: Relevance
“…The structure of the protein-ssDNA complex has been studied using electron microscopy and solution scattering methods and is found to consist of a regular left-handed superhelix in which the gene V protein dimers are arrayed on the outside of the superhelix and the ssDNA strands are inside (8,25). The structure of the gene V protein is also of interest because its small size and the large number of mutants available have made it a useful model for determining effects ofamino acid substitutions on protein stability and function (23,26,27).A model for the crystal structure of the wild-type (WT) gene V protein has been reported (28), but recent NMR studies have demonstrated that the positions of amino acids involved in the segments of antiparallel (-structure are not compatible with those in the model (21), and a new determination of the structure was necessary. The multiwavelength anomalous diffraction (MAD) technique (29) was ideally suited for this purpose, as the WT gene V protein contains two methionine residues (Met-1 and Met-77) that might be substituted in vivo in Escherichia coli by selenomethionine.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The structure of the protein-ssDNA complex has been studied using electron microscopy and solution scattering methods and is found to consist of a regular left-handed superhelix in which the gene V protein dimers are arrayed on the outside of the superhelix and the ssDNA strands are inside (8,25). The structure of the gene V protein is also of interest because its small size and the large number of mutants available have made it a useful model for determining effects ofamino acid substitutions on protein stability and function (23,26,27).A model for the crystal structure of the wild-type (WT) gene V protein has been reported (28), but recent NMR studies have demonstrated that the positions of amino acids involved in the segments of antiparallel (-structure are not compatible with those in the model (21), and a new determination of the structure was necessary. The multiwavelength anomalous diffraction (MAD) technique (29) was ideally suited for this purpose, as the WT gene V protein contains two methionine residues (Met-1 and Met-77) that might be substituted in vivo in Escherichia coli by selenomethionine.…”
mentioning
confidence: 99%
“…Gene V protein binding to single-stranded nucleic acids and to oligonucleotides has been studied using chemical modification, spectroscopic techniques, and mutagenesis (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). The structure of the protein-ssDNA complex has been studied using electron microscopy and solution scattering methods and is found to consist of a regular left-handed superhelix in which the gene V protein dimers are arrayed on the outside of the superhelix and the ssDNA strands are inside (8,25).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the participation of Y41 in the protein dimer-dimer contacts in the GVP-ssDNA complex (King & Coleman, 1988;Stassen et al, 1992) was explained adequately. A similar model has been proposed independently using the three-dimensional structure of Y41H GVP determined by NMR Folmer et al, 1994).…”
mentioning
confidence: 94%
“…During the rolling circle replication process, GVP binds to the ssDNA cooperatively and, ultimately, a superhelical GVP-DNA complex is formed. The structure of such helical complexes has been studied by a number of biophysical methods, including electron microscopy (Gray, 1989;Olah et al, 1995), neutron scattering (Gray et al, 1982;Olah et al, 1995), NMR and fluorescence spectroscopies (King & Coleman, 1987Dick et al, 1989;Stassen et al, 1992;Folkers et al, 1993). The results of these studies have provided valuable insights regarding the interactions of GVP and ssDNA.…”
mentioning
confidence: 99%